Attitudes of Consumers from University of Novi Sad toward Advertising through Sport among the Question how Often they Participate in Sports Activities - Dusko Bjelica; Marko Gušić; Nebojša Maksimović (Journal of Anthropology of Sport and Physical Education, 2018)
This research was aimed at gaining relevant knowledge about the attitudes of University of Novi Sad consumers toward advertising through sport among the question how often they participate in sports activities. The sample included 168 students from Faculti of Sporth and Physical Education in Novi Sad, divided into six subsample groups: consumers who do not participate in sport activities at all, then consumers who participate in sport activities less than ones a month, next 1–4 a month, 5–10 a month, 11–20 a month, as well as consumers participate in sport activities more than 20 times a month. The sample of variables contained the system of three general attitudes which were modelled by seven-point Likert scale. The results of the measuring were analyzed by multivariate analysis (MANOVA) and univariate analysis (ANOVA) and Post Hoc test. Based on the statistical analyses it was found that significant differences occur at multivariate level, as well as between all three variables at a significance level of p=.000. Hence, it is interesting to highlight that it was found there are significant differences showed up between the consumers who participate in various sports activities. The significant differences were found in one of three variables, while the consumers who participate less than 4 times a moths had much more negative attitudes toward advertising though sport.